Pengaruh Transkripsi Instan Terhadap Pemahaman Mahasiswa Tunarungu Universitas Sebelas Maret - Putri, Andika Arfiana; Anwar, Mohammad; Anggrellanggi, Arsy (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
This research aims to determine the effect of using instant transcription on the understanding of deaf students.  This research uses an experimental approach with a pre-test post-test control group design. The sample in this study were 6 students and the sample was taken with Non-probability sampling technique with saturated sampling type. The data analysis technique used in this study was the Mann Whitney U-Test. The results of data analysis showed that the average post-test score of the experimental group was 59.62, which was higher than the control group which only had an average score of 43.32. In this study, it can be concluded that Instant Transcription affects the understanding of deaf students.